2018
DOI: 10.1007/s12471-018-1151-z
|View full text |Cite
|
Sign up to set email alerts
|

Attention needed for cognitive problems in patients after out-of-hospital cardiac arrest: an inventory about daily rehabilitation care

Abstract: AimRecent literature and Dutch guidelines for patients with out-of-hospital cardiac arrest (OHCA) recommend screening for cognitive impairments and referral to cognitive rehabilitation when needed. The aim of this study is to assess the uptake of these recommendations for OHCA patients.MethodAn internet-based questionnaire was sent to 74 cardiologists and 143 rehabilitation specialists involved in rehabilitation of OHCA patients in the Netherlands. The questionnaire covered: background characteristics, availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…Secondly, the limited response rate may have affected the generalizability of the results, since those with an interest in eRehabilitation may have been more willing to participate and may have perceived other barriers and facilitators to the use of eRehabilitation compared with those who did not respond. However, the response rate of the current study is comparable with that in other rehabilitation studies (33,34), and the age and sex of responders did not differ from those of the non-responders. In addition, the age of our responders may seem low, but the Dutch medical specialist rehabilitation setting does not included geriatric rehabilitation care, which explains why the study sample was relatively young.…”
Section: Discussionsupporting
confidence: 84%
“…Secondly, the limited response rate may have affected the generalizability of the results, since those with an interest in eRehabilitation may have been more willing to participate and may have perceived other barriers and facilitators to the use of eRehabilitation compared with those who did not respond. However, the response rate of the current study is comparable with that in other rehabilitation studies (33,34), and the age and sex of responders did not differ from those of the non-responders. In addition, the age of our responders may seem low, but the Dutch medical specialist rehabilitation setting does not included geriatric rehabilitation care, which explains why the study sample was relatively young.…”
Section: Discussionsupporting
confidence: 84%
“…Post-cardiac arrest care has previously been mapped in Sweden and the Netherlands but these studies focused on the post-hospital discharge phase, i.e. the provision of out-patient clinic follow-up to survivors and families 17 and screening for cognitive impairments and referral to cognitive rehabilitation 18 . Results showed that these post-hospital care elements were far from successfully implemented despite existing international recommendations for rehabilitation after cardiac arrest 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Post cardiac arrest care has previously been mapped in Sweden and the Netherlands but these studies focused on the post-hospital discharge phase, i.e. the provision of out-patient clinic follow-up to survivors and families 17 and screening for cognitive impairments and referral to cognitive rehabilitation 18 . Mapping the provision of cardiac rehabilitation to survivors of cardiac arrest can inform future development, adoption and implementation of rehabilitation services to the survivors but, to our knowledge, have not previously been undertaken.…”
Section: Introductionmentioning
confidence: 99%
“…A large majority (89%) of healthcare providers involved in care for OHCA patients support the idea of a combined cardiac and cognitive program after cardiac arrest. However, this same survey showed that cognitive and emotional screening tools are not taken out routinely and not all patients are offered cardiac rehabilitation [27].…”
Section: Integrated Rehabilitation Care Pathmentioning
confidence: 99%